Developing Transnational Indigenous Solidarity: The Case of Borneo Dayak Forum (Department of International Relations, Universitas Brawijaya, 2021)
Dayak people are an indigenous community inhabiting the Island of Borneo. They dub themselves as the natives and the inheritance of the island’s heritage and culture. Before the intrusion of colonial influences, they were prosperous and great, but now they are ironically struggling to revive and retrace their ancestral heritage in their own home. This article seeks to explain and analyze the effort of the Dayak community to advocate for their rights and culture by developing a transnational advocacy network called Borneo Dayak Forum to promote sustainable living. This network serves as a platform that Dayak people capitalize upon to influence policy-making in Indonesia in which Dayak people currently inhabit especially in Kalimantan Island. This article argues BDF has played a significant role in promoting Dayak people's agendas in achieving sustainable living, especially in the realm of the preservation of customary law and protection of indigenous lands.